2020
DOI: 10.3389/fphar.2020.01321
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin Induces Apoptosis and Promotes Differentiation of AML Cells Through Nuclear Receptor Nur77-Mediated Signaling Pathway

Abstract: Background Acute myeloid leukemia (AML) is a hematopoietic malignancy characterized by uncontrolled proliferation and accumulation of myeloblasts in the bone marrow (BM), blood, and other organs. The nuclear receptors Nur77 is a common feature in leukemic blasts and has emerged as a key therapeutic target for AML. Cantharidin (CTD), a main medicinal component of Mylabris (blister beetle), exerts an anticancer effect in multiple types of cancer cells. Purpose This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that NUR77 , which encodes nuclear receptor subfamily 4 group A member 1, plays an important role in tumor suppression in acute myeloid leukemia. Specifically, Zanyang et al [ 22 ]. reported that cantharidin induced NUR77 expression, significantly inhibiting viability and colony formation in acute myeloid leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that NUR77 , which encodes nuclear receptor subfamily 4 group A member 1, plays an important role in tumor suppression in acute myeloid leukemia. Specifically, Zanyang et al [ 22 ]. reported that cantharidin induced NUR77 expression, significantly inhibiting viability and colony formation in acute myeloid leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cantharidin (CTD) is the main bioactive component of cantharidin. Recent studies have found that CTD and its derivatives, such as Cantharidic acid and norcantharidin, inhibit leukemia cell proliferation, induce apoptosis, cause cell cycle arrest and enhance the inhibitory effect of chemotherapeutic drugs [ 34 , 35 , 36 ]. Notopterol, a coumarin, is an active monomer extracted from N. incisum with antipyretic, analgesic, and anti-inflammatory properties.…”
Section: Hematologic Tumorsmentioning
confidence: 99%
“…The molecular formula of CTD is C 10 H 12 O 4 , and the molecular weight is 196.2 g/mol. CTD has been confirmed to exert inhibitory effects on multiple types of cancers, such as liver cancer [ 3 ], acute myeloid leukemia [ 4 ], pancreatic cancer [ 5 ], gastric cancer [ 6 ], breast cancer [ 7 ], osteosarcoma [ 8 ] and lung cancer [ 9 ]. Moreover, it could recruit white blood cells, and may potentiate immune response [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%